2022
DOI: 10.3390/molecules27092692
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic Synthesis of Fatty Acid Isoamyl Monoesters from Soybean Oil Deodorizer Distillate: A Renewable and Ecofriendly Base Stock for Lubricant Industries

Abstract: In this study, soybean oil deodorizer distillate (SODD), a mixture of free fatty acids and acylglycerides, and isoamyl alcohol were evaluated as substrates in the synthesis of fatty acid isoamyl monoesters catalyzed by Eversa (a liquid formulation of Thermomyces lanuginosus lipase). SODD and the products were characterized by the chemical and physical properties of lubricant base stocks. The optimal conditions to produce isoamyl fatty acid esters were determined by response surface methodology (RSM) using rota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 73 publications
0
2
0
Order By: Relevance
“…Table 4 shows the results obtained for the product synthesized (0.985 purity) in a reaction developed at optimal conditions with a 0.985. Upon comparing the viscosity index of the ester under study with those of other biolubricants described in the consulted bibliography [11][12][13]16,17,21,26,29,30], it is evident that the value calculated in this work (204.43) falls within the range of those found in the studies of other researchers (above 150). Therefore, it can be concluded that this ester is good enough for use as a biolubricant because it maintains its viscosity over a broad temperature range, ensuring consistent performance and protection against wear and tear, even in extreme conditions.…”
Section: The Characterization Of 2-octyl-1-dodecanoyl 2-methylhexanoa...supporting
confidence: 65%
See 1 more Smart Citation
“…Table 4 shows the results obtained for the product synthesized (0.985 purity) in a reaction developed at optimal conditions with a 0.985. Upon comparing the viscosity index of the ester under study with those of other biolubricants described in the consulted bibliography [11][12][13]16,17,21,26,29,30], it is evident that the value calculated in this work (204.43) falls within the range of those found in the studies of other researchers (above 150). Therefore, it can be concluded that this ester is good enough for use as a biolubricant because it maintains its viscosity over a broad temperature range, ensuring consistent performance and protection against wear and tear, even in extreme conditions.…”
Section: The Characterization Of 2-octyl-1-dodecanoyl 2-methylhexanoa...supporting
confidence: 65%
“…To date, biocatalytic synthesis has been extensively developed. The esterification and transesterification of a wide variety of fatty acid-composed materials with different alcohols and poliols (methanol, neopentyl glycol, isoamyl alcohol, trimethylolpropane, pentaerythritol and fusel oil) have been catalyzed by lipases, both free and immobilized, from different sources, in solvent-free systems to yield first-generation biolubricants [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…Different experimental conditions were explored to minimize enzyme inhibition and optimize ester production. All reactions were carried out in solvent-free systems, which make this synthesis methodology even more attractive from economic and environmental points of view [69][70][71][72].…”
Section: Introductionmentioning
confidence: 99%
“…These properties of lipases demonstrate their good performance when applied in biocatalysis in the most diverse processes [ 4 ]. For example, in studies on biolubricants [ 7 ], the synthesis of glycerin monostearate [ 8 ], biosurfactant production [ 9 ], in the pretreatment of industrial [ 10 ], in the production of new nanobiocatalysts [ 11 ], and in the modification of cheese by enzymes [ 12 ].…”
Section: Introductionmentioning
confidence: 99%